Electricity demand forecast of Turkey based on hydropower and windpower potential - Donmez, Aydin Haci; Karakoyun, Yakup; Yumurtaci, Zehra (TAYLOR & FRANCIS INC, 2017)
Turkey is a developing country and its energy requirement is increasing with each passing day. The most important energy sources of Turkey are natural gas, coal, and hydropower. Almost all of the natural gas and one-third of the coal are imported; thus, in order to utilize the national sources, hydropower has vital importance. Moreover, wind energy is also an important factor owing to Turkey's quite good wind chart. This study discusses the evaluation of the renewable energy potential of Turkey. In detail, the hydropower and windpower potentials, installed capacities, and developments are investigated. The study is extended with the various electricity demand projections existing in the literature. As a result, it is clearly seen that the official electricity demand prediction is much higher than the other prediction values. Moreover, the second-order curve fitting model gives the closest results to the official demand values among all other models.
Keywords: Electricity demand prediction; energy potential; hydropower; renewable energy; windpower; VISION 2023; CONSUMPTION; Energy & Fuels